A multi-decadal geochemical record from Rano Aroi (Easter Island/Rapa Nui): Implications for the environment, climate and humans during the last two millennia. (15th September 2021) - Roman, Marco; McWethy, David B.; Kehrwald, Natalie M.; Erhenhi, Evans Osayuki; Myrbo, Amy E.; Ramirez-Aliaga, José M.; Pauchard, Anibal; Turetta, Clara; Barbante, Carlo; Prebble, Matthew; Argiriadis, Elena; Battistel, Dario
Abstract: The small and remote Easter Island (Rapa Nui) has a complex and still partially unknown history of human colonization and interactions with the environment. Previous research from sedimentary archives collected in the three freshwater bodies of Rapa Nui document dramatic environmental changes over the last two millennia. Yet, the characteristics of sediments and paleoenvironmental records are challenging to interpret, mainly due to poor temporal resolution, hiatuses and sediment mixing. In this study, we reconstruct past changes in lithogenic inputs, weathering processes, redox conditions, productivity and water levels in the Rano Aroi wetland over the last 2000 years through the determination of major, trace and rare earth elements in a new peat core collected in 2017. The chronology is based on 8 14 C AMS dates for the upper 1.5 m and provides decadal to multi-decadal resolution which is unprecedented for the island of Rapa Nui. The multielemental proxies depict seven distinct chronological phases marked by well-defined geochemical transitions. With only a few minor fluctuations, climate conditions were dry and the mire was mildly anoxic during the first millennium (0–1000 CE) to the arrival of the first Polynesians in Rapa Nui (800–1300 CE) and until ∼1400 CE, followed by wetter conditions afterwards. The record documents with unprecedented accuracy and resolution intense droughts occurring during the middle Little Ice Age between 1520 and 1710 CE, which may have been exacerbated by human activities and triggered dramatic cultural shifts. During the interval of first contact between the Rapanuis and Europeans, the climate changed to wetter conditions, followed by intense precipitations between 1790 and 1900 CE. Highlights : Multielemental proxies depict seven geochemical phases at Rano Aroi during the last 2000 years. Local rainfall is the primary driver; clear connection with regional climate cannot be inferred. Intense droughts between 1520 and 1710 CE are documented with unprecedented accuracy/resolution. Between 1520 and 1710 the Rapanui responded to/exacerbated a changing climatic pattern.